Iron and the female athlete: a review of dietary treatment methods for improving iron status and exercise performance - Alaunyte, I.; Stojceska, V.; Plunkett, A. (Journal of the International Society of Sports Nutrition, 2015)
Iron is a functional component of oxygen transport and energy production in humans and therefore is a critically important micronutrient for sport and exercise performance. Athletes, particularly female athletes participating in endurance sport, are at increased risk of compromised iron status due to heightened iron losses through menstruation and exercise-induced mechanisms associated with endurance activity. Conventionally oral iron supplementation is used in prevention or/and treatment of iron deficiency. However, this approach has been criticised because of the side effects and increased risk of iron toxicity associated with the use of supplements. Thus, more recently there has been a growing interest in using dietary modification rather than the use of supplements to improve iron status of athletes. Dietary iron treatment methods include the prescription of an iron-rich diet, or/and haem iron-based diet, dietary advice counselling and inclusion of novel iron-rich products into the daily diet. Although studies using dietary modification are still scarce, current literature suggests that dietary iron interventions can assist in maintaining iron status in female athletes, especially during intensive training and competition. Future research should focus on the most efficient method(s) of dietary modification for improvement of iron status and whether these approaches can have a favourable impact on sports and exercise performance.